2018
DOI: 10.1097/scs.0000000000004316
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Measurements of Bony Nasolacrimal Canal in Children

Abstract: Our study demonstrated that development of BNLD continues during childhood, regardless of gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Studies pertaining to the nasolacrimal duct have shown that the females often have narrow canals than males. 8,23 The diameter was also reported to be smaller in Caucasians. 4,7 In this study, the nasolacrimal canal was compared between male and female and was found to be greater in females which was quite opposite to the other studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies pertaining to the nasolacrimal duct have shown that the females often have narrow canals than males. 8,23 The diameter was also reported to be smaller in Caucasians. 4,7 In this study, the nasolacrimal canal was compared between male and female and was found to be greater in females which was quite opposite to the other studies.…”
Section: Discussionmentioning
confidence: 96%
“…4,7 In this study, the nasolacrimal canal was compared between male and female and was found to be greater in females which was quite opposite to the other studies. 7,8,23 Fasina et al reported the mean diameter of nasolacrimal canal of 3.52 mm in men and 3.36 mm in female. 24 This was also in sharp contrast to the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these clinical studies, there were a few radiologic studies focusing on morphometry of the NLD. [1,5,6,21] Ela et al [6] studied the morphometry of NLD on children, while Czyz et al [5] examined the NLD morphometry according to aeration grades in adult participants. However, they could not find any significant differences for morphometric values of the NLD between age and genders.…”
Section: Discussionmentioning
confidence: 99%
“…There are numbers of studies that are evaluating the morphometric properties of the NLD. [5][6][7] The NLD has different anthropometric characteristics among populations. [1,4,[7][8][9] Avdagic et al [10] indicated that NLD obstruc-tions could count as an important etiologic factor of epiphora, and emphasized that selecting criteria for treating these obstructions depends on its anatomical properties.…”
Section: Introductionmentioning
confidence: 99%